2020
DOI: 10.7203/relieve.26.2.17611
|View full text |Cite
|
Sign up to set email alerts
|

Análisis psicométrico de una prueba para evaluar la competencia digital de estudiantes de Educación Obligatoria

Abstract: Para que las investigaciones sobre la competencia digital puedan aportar información valiosa que contribuya a guiar las políticas educativas de desarrollo de la misma y de integración de las Tecnologías de la Información y la Comunicación en los sistemas educativos de los países, es necesario contar con instrumentos de recogida de información válidos y fiables. El objetivo del presente trabajo es el de validar una prueba para evaluar la competencia digital en estudiantes de Educación Obligatoria, en los … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
0
5
0
9
Order By: Relevance
“…These items are each formed as multiple-choice questions with one correct answer (scored as "1") and three incorrect answers (scored as "0"). Therefore, original analysis procedures were followed (Casillas-Martín et al, 2020) considering the total score for each competency as a numerical variable from 0 to 4 points. The second domain, "attitude," consists of general affirmations regarding the digital information competence, with six items based on a 5-point, ordinal Likert-type scale (1 = strongly disagree, 2 = disagree, 3 = indifferent, 4 = agree, and 5 = strongly agree).…”
Section: Instrumentmentioning
confidence: 99%
See 2 more Smart Citations
“…These items are each formed as multiple-choice questions with one correct answer (scored as "1") and three incorrect answers (scored as "0"). Therefore, original analysis procedures were followed (Casillas-Martín et al, 2020) considering the total score for each competency as a numerical variable from 0 to 4 points. The second domain, "attitude," consists of general affirmations regarding the digital information competence, with six items based on a 5-point, ordinal Likert-type scale (1 = strongly disagree, 2 = disagree, 3 = indifferent, 4 = agree, and 5 = strongly agree).…”
Section: Instrumentmentioning
confidence: 99%
“…It evaluates the five areas of the DigComp through subscales, one of which is the "ECODIES -Area 1: Information" subscale. The original psychometric study showed appropriate results of its validity (Casillas-Martín et al, 2020). This competence plays a crucial role in school-based student learning in the current education environment (Harju et al, 2019), and also in preventing the proliferation of fake news (Jones-Jang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las competencias digitales, entendidas como el conjunto de capacidades y habilidades que permiten a las personas ser responsables y críticas ante los medios, ser capaces de buscar, procesar, comunicar, crear y difundir información por medio de las tecnologías (Ferrés y Piscitelli, 2012;Pérez-Rodríguez y Delgado-Ponce, 2012) se han convertido en competencias fundamentales en la formación de la ciudadanía (Atchoarena et al, 2017;González et al, 2018) e imprescindibles para el aprendizaje permanente (Casillas-Martín et al, 2020), porque permiten a las personas adaptarse al ecosistema mediático actual, siendo responsables y reflexivas en el uso de las TIC (Tejada y Pozos, 2018).…”
Section: Las Competencias Digitales Y La Privacidad Onlineunclassified
“…This is when they can receive documentation. Nevertheless, attending to physical factors is not enough to evaluate a minor's age and other individual, social and cultural factors must also be considered (Garamendi et al, 2011;Cemlyn and Nye, 2012;Bravo and Santos-González, 2017;Ambrosini, 2018;Casillas-Martín et al, 2020). Thus, the determination of age is fundamental, as is belonging to a reception center, where residential care programs are developed.…”
Section: Introductionmentioning
confidence: 99%